Teaching and learning an ethnic minority language at university level: the case of Dusun in Brunei - Najib Noorashid; McLellan, James (Penerbit Universiti Kebangsaan Malaysia, 2018)
This article investigates the teaching and learning of an ethnic minority language at tertiary level as a strategy for language maintenance and revitalisation. We offer a case study of the Dusun language, which is taught as a breadth/elective course at the Language Centre in Universiti Brunei Darussalam. Although the initial purpose of introducing ethnic language courses was to encourage students to be familiar with the practices and the cultural knowledge associated with the community of users, their role in language maintenance is also worthy of investigation. The research methods include classroom observations, a questionnaire survey and analysis of examination results. The observation and the survey assist in the understanding of students’ reactions to the curriculum. We find that offering Dusun as a credit-bearing language module (course) has generated interest among both students and the wider Brunei community. Those from Dusun family backgrounds taking the module are a minority: most students have no family connections with Dusun. The implementation of the curriculum remains problematic, and there are issues resulting from the need to meet the formal requirements and academic expectations of the university administration in terms of coursework and examinations. The absence of dictionaries, grammars and other pedagogical materials means that Dusun language teachers are obliged to develop their own materials and resources. We argue that offering Borneo minority indigenous languages at tertiary level may not in itself maintain or revive the language in question, but is one strategy, along with several others, which may help towards maintenance and revitalisation.